The Effect of U-Bends on the Convective Heat Transfer Coefficient of Nanofluids Flow - Alamirsyah Alamirsyah; Adek Tasri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2026)
One effort that can increase the convection heat transfer coefficient between fluid and solid surface is adding nanoparticles to the fluid. However, there are several flow-path conditions, such as concavities and U-turns, can affect the distribution of nanoparticles in the fluid and, in turn, the heat transfer coefficient. This paper studies the effect of a U-turn on the transfer coefficient. The study was conducted using numerical simulations to determine changes in the heat transfer coefficient along the U-turn. It was found that the convection heat transfer coefficient increased at several locations on the outside of the U-turn. The heat transfer coefficient also increased at several locations on the inside of the bend, though by smaller amounts.